Biting cold : a Chicagoland vampires novel - Neill, Chloe (Neill, Chloe. Chicagoland vampires novel, 2012)
Merit is on the hunt, charging across the stark American Midwest to tail a rogue supernatural intent on stealing an ancient artifact that could unleash catastrophic evil on the world.